RAFTING, SEBUAH USAHA YANG MEMANFAATKAN ALIRAN SUNGAI DI BALI - A.A. Bagus Wirateja; A.A. Ngr Gede Suindrawan (Universitas Triatma Mulya, 2022)
Diversification of tourist attraction need to be developed more in order to increase the number of the tourist to visit Indonesia. If it is reached so it would be able to rise the Nation Income. There are many potential on natural resources that we have, especiallt many long rivers are available and seem proper for rafting. Rafting activity then brings vary of choices for guests who loved activities in nature background. All of us have realized that rafting will have some impacts on the environment along the rivers banks and the people who live there. Actually the activities will make a good and bad impact on the environment. However we have to consider maximizing the good impact and try to minimize the bad impact in order to give and advantage over environment conservation and local people around the spot.